Muslim Scholars’ Perception Of Coronavirus (Covid-19) - An Analytical Study - Md Saiful Islam; Md Redowanul Karim (Universiti Sains Islam Malaysia, 2024)
Proceedings of the 7th International Prophetic Conference (SWAN) 2020 FPQS,Universiti Sains Islam Malaysia, 29-30 October 2020 Paper No. BI006 60-64